Cognitive Moral Development and Its Relevance in Establishing Moral Integrity in Organization (Sains Humanika, 2021)
Integrity is one of the most important values in organization’s life. A common approach used in defining integrity is to associate the concept with particular ethical behavior, so often the approach taken is to encourage every individual in the organization to act in accordance with the expected behaviors. Integrity is associated with decision-making process in which the development of moral cognitive influences. In reality, not all stages of cognitive moral development are supporting the establishment of integrity. Only the sixth stage of moral development which is oriented to universal moral values that can support the formation of integrity. By using philosophical critical analysis approach, this paper aims to explain conceptually how cognitive moral development plays role in the formation of integrity of the self and the consequence in shaping culture in organization. It concludes that creating organizational culture of integrity needs not only to think about how to shape the behavior of members of the organization in line with the behavior expected by the organization, but at the same time how to form moral consciousness oriented to universal moral values.
Keywords: Integrity; morality; moral cognitive development; organizational culture; value